The role of dietary phytochemicals in the carcinogenesis via the modulation of miRNA expression - Samec, Marek; Liskova, Alena; Kubatka, Peter; Uramova, Sona; Zubor, Pavol; Samuel, Samson Mathews; Zulli, Anthony; Pec, Martin; Bielik, Tibor; Biringer, Kamil; Kudela, Erik; Benacka, Jozef; et al. (Journal of cancer research and clinical oncology, 2019)
PURPOSE: Phytochemicals are naturally occurring plant-derived compounds and some of them have the potential to serve as anticancer drugs. Based on recent evidence, aberrantly regulated expression of microRNAs (miRNAs) is closely associated with malignancy. MicroRNAs are characterized as small non-coding RNAs functioning as posttranscriptional regulators of gene expression. Accordingly, miRNAs regulate various target genes, some of which are involved in the process of carcinogenesis. RESULTS: This comprehensive review emphasizes the anticancer potential of phytochemicals, either isolated or in combination, mediated by miRNAs. The ability to modulate the expression of miRNAs demonstrates their importance as regulators of tumorigenesis. Phytochemicals as anticancer agents targeting miRNAs are widely studied in preclinical in vitro and in vivo research. Unfortunately, their anticancer efficacy in targeting miRNAs is less investigated in clinical research. CONCLUSIONS: Significant anticancer properties of phytochemicals as regulators of miRNA expression have been proven, but more studies investigating their clinical relevance are needed.
Keywords: Neoplasms; nádory; Animals; karcinogeneze; fytogenní protinádorové látky; Antineoplastic Agents, Phytogenic; MicroRNAs; microRNAs; lidé; Phytochemicals; zvířata; Cancer; mikro RNA; Carcinogenesis; Plant-derived food; Humans